1990
DOI: 10.1111/j.1365-2958.1990.tb00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of Enterococcus faecalis aggregation substance encoded by the sex pheromone plasmid pAD1

Abstract: The location of the structural gene for aggregation substance on the sex pheromone plasmid pAD1 of Enterococcus faecalis was determined using an oligonucleotide deduced from the N-terminal amino acid sequence of the purified protein. The nucleotide sequence was determined for the corresponding region and two open reading frames (ORFs) could be identified. ORF1 codes for a small (Mr 13,160) acidic protein of unknown function. The gene for aggregation substance (named asa1) was found to code for a protein of 129… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(122 citation statements)
references
References 33 publications
2
120
0
Order By: Relevance
“…By using the 3D-PSSM-fold recognition server (Kelley et al, 2000), we initially found 14 enterococcal CWA proteins with predicted Ig-like folds among the panel of 29 putative CWA proteins identified by us. Four of these are highly conserved aggregation substance (Galli et al, 1990(Galli et al, , 1992 homologues (77 % overall identity in multiple alignment) and one shows significant similarity (31 % identity over 1457 aa) to the biofilm-associated protein (Bap) of S. aureus (Cucarella et al, 2001). As we were focusing on novel and uncharacterized CWA proteins with MSCRAMM-like structural features, we chose the remaining nine proteins (EF0089, EF1091, EF1092, EF1093, EF1099, EF1269, EF1824, EF2224 and EF3023; TIGR annotation locus names have been used throughout this study) for further investigation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By using the 3D-PSSM-fold recognition server (Kelley et al, 2000), we initially found 14 enterococcal CWA proteins with predicted Ig-like folds among the panel of 29 putative CWA proteins identified by us. Four of these are highly conserved aggregation substance (Galli et al, 1990(Galli et al, , 1992 homologues (77 % overall identity in multiple alignment) and one shows significant similarity (31 % identity over 1457 aa) to the biofilm-associated protein (Bap) of S. aureus (Cucarella et al, 2001). As we were focusing on novel and uncharacterized CWA proteins with MSCRAMM-like structural features, we chose the remaining nine proteins (EF0089, EF1091, EF1092, EF1093, EF1099, EF1269, EF1824, EF2224 and EF3023; TIGR annotation locus names have been used throughout this study) for further investigation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…asal (coding for ASAl = aggregation substance of pAD1) was the first gene of a sex pheromone plasmid to be sequenced (Galli et al, 1990). When the sequence for the homologous gene from pCFlO was established (Kao et al, 1991) it became clear that the genes are highly conserved.…”
Section: Sequence Of the Plasmid Encoded Adhesinsmentioning
confidence: 99%
“…Two different forms of Agg have been described: Asa1 and Asa373 (De Boever et al, 2000;Galli et al, 1990). Previously, we reported that E. faecalis expressing Agg adheres in significantly higher numbers to biomaterials compared with isogenic strains without Agg.…”
Section: Introductionmentioning
confidence: 99%